Persistence of immunogenicity, contributing factors of an immune response, and reactogenicities after a single dose of the ChAdOx1 (AZD1222) COVID-19 vaccine in the Thai population. Issue 1 (31st January 2022) - Tawinprai, Kriangkrai; Siripongboonsitti, Taweegrit; Porntharukchareon, Thachanun; Dechates, Bothamai; Monprach, Harnphadungkit; Sornsamdang, Gaidganok; Wittayasak, Kasiruck; Soonklang, Kamonwan; Mahanonda, Nithi
ABSTRACT: Introduction: Due to the vaccine's short supply and the efficacy of a single dose of the ChAdOx1 (AZD1222) vaccine, many governments delayed the interval between prime and boost dose from 4 to 8–12 weeks. However, the waning of immune response in this period is a concern. This study evaluated the durability, contributing factors of anti-RBD antibody concentration, and reactogenicities after the single dose of AZD1222 vaccine in the Thai population. Methods: This was a single-center, prospective cohort study at Chulabhorn Hospital, Bangkok, Thailand. Individuals 18 years or older who were negative for anti-SARS-CoV-2 antibody were eligible. Anti- receptor-binding domain antibody concentrations were tested at least three weeks after the first vaccination and immediately before the second dose of vaccine. Information on reactogenicities was obtained via a questionnaire sent by a short message service. Results: Anti-RBD Antibody concentration at 2 and 3 months post-vaccination were significantly higher than at 1 months post-vaccination (20.14 BAU/mL (95%CI; 16.37, 24.77) at 1 month, 48.08 BAU/mL (95%CI; 42.76, 54.08) at 2 month, and 65.01 BAU/mL (95%CI; 58.88, 71.61) at 3 month). Adverse events occurred in approximately 60% of participants. Factors influencing vaccine immunogenicity include age, sex, the time elapsed from the first dose of vaccine, and underlying disease with diabetes and hematologic disease. Conclusion: A single dose of AZD1222 could elicit immune responses that did not decline within three months in Thai individuals. These data support the public health strategy of a delay between the prime and boost dose of AZD1222 of 4 to 12 weeks.